2016
DOI: 10.1038/am.2016.142
|View full text |Cite
|
Sign up to set email alerts
|

Towards a comprehensive understanding of FeCo coated with N-doped carbon as a stable bi-functional catalyst in acidic media

Abstract: The identification and development of efficient catalysts made of non-precious materials for oxygen reduction reaction (ORR) are essential for the successful operation of a wide range of energy devices. This study provides evidence that earth-abundant nanoparticles of transition metals encapsulated in a nitrogen-doped carbon shell (M@N-C, M = Fe, Co, Ni, Cu or Fe alloys) are promising catalysts in acidic solutions. By density functional theory calculations and experimental validations, we quantitatively propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 56 publications
(66 reference statements)
1
52
0
3
Order By: Relevance
“…showed that an increase of the nitrogen concentration can stabilize the *O intermediate as the *OH and *OOH intermediates remain mostly unaffected, whereas our own previous study highlighted the importance of *O coverage relative to the N doping concentration . However, we expect that the trend in the ORR activity caused by the different introduced metal atoms into the Fe 3 C substrate is largely insensitive to the substrate, as found previously by Noh et al . for Fe, Co, Ni, and Cu nanoparticles encapsulated by N‐doped carbon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that an increase of the nitrogen concentration can stabilize the *O intermediate as the *OH and *OOH intermediates remain mostly unaffected, whereas our own previous study highlighted the importance of *O coverage relative to the N doping concentration . However, we expect that the trend in the ORR activity caused by the different introduced metal atoms into the Fe 3 C substrate is largely insensitive to the substrate, as found previously by Noh et al . for Fe, Co, Ni, and Cu nanoparticles encapsulated by N‐doped carbon.…”
Section: Resultsmentioning
confidence: 99%
“…These results are explained by Δ E int and related to the segregation. In an alloy compound, the component with a low surface energy tends to segregate to the surface, and the difference in energy required to form the surface between the constituent components will drive the segregation . In the case of Co, Δ E int of Co is lower than that of Fe, which suggests that Co is more likely to form a surface layer than Fe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction of metal onto N‐doped carbon matrix is a promising strategy for optimization of the electronic structure of carbonaceous framework and the adsorption free energy of H + and OH − reactants, thus, facilitating the electrocatalytic process . Many reports exist for supporting FeCo alloy on heteroatom doped carbonaceous material as excellent oxygen evolving electrocatalysts . For example, bimetallic FeCo alloy NPs can be used for in‐situ growth of CNTs which not only controls the agglomeration of NPs by confining them in their protective graphitic wall but also provide an electron highway .…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 1A, it is possible to observe the presence of oxides, metallic nanoparticles, nitrides and carbides (some peaks are overlapped). Considering that some of these structures were reported to be active for the ORR, especially in alkaline media [23,24,37,38], the acid treatment was conducted in order to remove most of these secondary structures. It is noted that the diffraction patterns in (B) are similar for all samples.…”
Section: Introductionmentioning
confidence: 99%